Weissella paramesenteroides: A Lactic Acid Bacteria Producing Glutathione from Fermented Vegetable Based Keciwis Leaf - Luthfia Hastiani Muharram; Haryanto; Wulan Pertiwi; Nelis Hernahadini; Ima Mukaromah (Jurnal Biodjati, 2025)
Glutathione (GSH), is one of the essential antioxidants to prevent free radicals and support the immune system. The low level of glutathione is associated with some diseases such as cancer, Alzheimer’s, Parkinson’s, and AIDS. Lactic acid bacteria (LAB) can produce glutathione. Indonesia, as a mega biodiversity country, has various vegetables and LAB sources that remain underexplored. This research aims to explore LAB-producing glutathione from fermented products derived from Indonesia’s typical plant, the keciwis leaf. The method of this research includes sample preparation, lactic acid bacteria isolation, secondary metabolite production with cysteine precursor addition, glutathione analysis by Ellman’s assay, identification of 16S rRNA gene of lactic acid bacteria, and glutathione qualitative analysis by HPLC. Fermented keciwis leaf-based products contain lactic acid bacteria with positive gram characteristics, can produce 0.33 – 0.37 mM extracellular glutathione. Precursor cysteine addition significantly increases glutathione (p<0,05). The selective lactic acid bacteria producing glutathione was identified as belonging to the genus Weissella, with a similarity value of 98.50%, closely related to Weissella paramesenteroides. Extracellular glutathione produced by this culture showed qualitative results on HPLC with a retention time of 6.34 minutes, indicating the presence of the sulfihydryl group. This study identified a new Indonesia source of lactic acid bacteria of Indonesian–origin lactic acid bacteria, specifically Weissella paramesenteroides, as a promising source for glutathione production